To simplify the expression, we can apply the Power Rule of Exponents, which states that when raising an exponent expression to another exponent, we multiply the exponents.
Therefore,
(6^2)^4 = 6^(2*4) = 6^8
Use the Power Rule of Exponents to simplify the expression (6^2)^4 .
7 answers
(73^4)^5
To simplify the expression, we apply the Power Rule of Exponents, which states that when raising an exponent expression to another exponent, we multiply the exponents.
Therefore,
(73^4)^5 = 73^(4*5) = 73^20
Therefore,
(73^4)^5 = 73^(4*5) = 73^20
(78^8)^6
To simplify the expression, we apply the Power Rule of Exponents, which states that when raising an exponent expression to another exponent, we multiply the exponents.
Therefore,
(78^8)^6 = 78^(8*6) = 78^48
Therefore,
(78^8)^6 = 78^(8*6) = 78^48
what exponent would make the 2 expressions equivalent: (16x)^6 = (16^18)
To find the exponent that would make the two expressions equivalent, we need to set their exponents equal to each other and solve for x.
(16x)^6 = (16^18)
To do this, we can equate the exponents:
6 = 18
Since 6 is not equal to 18, there is no value of x that would make the two expressions equivalent.
(16x)^6 = (16^18)
To do this, we can equate the exponents:
6 = 18
Since 6 is not equal to 18, there is no value of x that would make the two expressions equivalent.